New Exact Solutions for a Higher-Order Wave Equation of KdV Type Using the Multiple Simplest Equation Method. (29th June 2014) - Zhao, Yun-Mei
Abstract : In our work, a generalized KdV type equation of neglecting the highest-order infinitesimal term, which is an important water wave model, is discussed by using the simplest equation method and its variants. The solutions obtained are general solutions which are in the form of hyperbolic, trigonometric, and rational functions. These methods are more effective and simple than other methods and a number of solutions can be obtained at the same time.